Regulatory Gaps in Drone Surveillance: Addressing Privacy, Security, and Manufacturing Standards - Siddiqui, Hassan Rasheed; Muniza, Maria (Annals of Human and Social Sciences, 2025)
This study aims to establish a comprehensive regulatory framework addressing privacy, security, and national concerns related to drones equipped with advanced facial recognition technology. As drones become more prevalent in surveillance, logistics, and law enforcement, existing regulations, such as those by the Federal Aviation Administration (FAA), fail to adequately address the privacy and security risks posed by these technologies. Despite the growth of digital privacy laws, aerial surveillance, particularly by drones, remains largely unregulated. This study analyzes current privacy laws, regulatory frameworks, and technological advancements in drone surveillance, focusing on privacy rights, national security, and the risks of cyberattacks. The research finds that current regulations are insufficient, particularly concerning unauthorized drone surveillance and national security risks, especially with foreign-made drones. The study highlights the need for stronger privacy protections, stricter manufacturing standards for foreign drones, and the use of blockchain technology to secure drone data and prevent cyberattacks. Recommendations include strengthening privacy laws for unauthorized drone use, tightening manufacturing standards, integrating blockchain for data security, and developing regulations based on the Fourth Amendment to protect citizens’ privacy. Additionally, the study suggests an import ban on Chinese drones to address potential security vulnerabilities. The research calls for immediate regulatory action to safeguard privacy and national security in the face of growing drone capabilities.